ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA BERBASIS PRODUCTIVE STRUNGGLE PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Vira Sutina; Karlimah; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a snakes and ladders learning media based on productive struggle for teaching plane shapes to elementary school students. The background of this research stems from students’ difficulties in understanding the concepts of plane shapes and the limited instructional media used by teachers. The productive struggle approach offers structured challenges that encourage students to solve problems independently, thereby enhancing conceptual understanding, learning autonomy, and mental resilience. This study adopts the Educational Design Research (EDR) method. Data collection techniques include interviews, observations, questionnaires, and expert validation. The analysis results show that most teachers and students require interactive and enjoyable learning media that can also stimulate students’ thinking skills. Game-based media such as snakes and ladders, when integrated with productive struggle principles, is considered highly suitable for development as it aligns with the characteristics of elementary school students. These findings form a crucial foundation for designing effective and contextual learning media to support mathematics.